Hubungan Antara Komunikasi Interpersonal Guru dengan Minat Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam di SMKN 3 Singkawang - Ummi Dzakiah; Dede Hidayat (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2024)
Interest is an impulse that comes from within a person, interest is an important factor in achieving good results. One effort that can foster students' interest in learning is the establishment of good interpersonal communication between teachers and students. The aim of this research is to determine the relationship between teacher interpersonal communication and students' interest in learning in class XI Islamic religious education subjects at SMKN 3 Singkawang. This type of research is quantitative research using the interactive correlation method, the population in the research is class XI students totaling 131 students. The technique used in sampling was random sampling, with a sample size of 40 students. Data collection techniques were carried out using questionnaires and documents. The data that has been collected is then analyzed using the product moment correlation analysis formula. The results of data analysis carried out using the Pearson product moment correlation technique obtained a value of 0.3784, while the critical r table with a correlation coefficient of N = 40 and a confidence value of α = 5% means the r table is 0.312. This shows that > atau 0,3784 > 0,312. Soit can be confirmed that there is a relationship between teacher interpersonal communication and students' interest in learning in class XI Islamic religious education subjects at SMKN 3 Singkawang for the 2022/2023 academic year. This analysis shows that the hypothesis is accepted.